Effect of rice rhizospheric Trichoderma spp and fungicide for the management of brown spot disease of rice - Kania, Hage; Pongener, Narola; Devi, Hijam Meronbala; Ao, N Tiameren; Devi, Hijam Shila (ORYZA-An International Journal of Rice, 2023)
Brown spot of rice caused by Bipolaris oryzae is of worldwide occurrence and is known to cause substantial quantitative and qualitative losses in grain yield. This disease was responsible for the epic 'Great Bengal Famine' in 1942-1943, resulting in the death of 4 million people. Studies were carried out to evaluate the effect of rice rhizospheric Trichoderma spp and fungicide for the management of brown spot disease of rice. A total of 20 isolates of Trichoderma spp were isolated from rice rhizospheric soil and screened by dual culture method in which three isolates Ti20, Ti19 and Ti16 showing maximum inhibition of 67.86%, 64.29% and 60.71% were selected for further test. Six fungicides viz., Hexaconazole, Propiconazole, Carbendazim + Mancozeb, Metalaxyl + Mancozeb, Carbendazim and Copper oxychloride were evaluated against B. oryzae by poison food technique, out of which Propiconazole, Hexaconazole and Copper oxychloride were selected and further tested for their compatibility with the selected Trichoderma spp was done. The most efficient and compatible Trichoderma sp with fungicide i.e., (Ti19 + Hexaconazole 5% SC) were selected for managing the disease in pot experiment with different treatment combinations i.e., seed treatment, seedling dip and foliar spray. Results under pot experiment showed that, seed treatment with Ti19 and Hexaconazole 5% SC recorded lowest disease severity of 3.70%, 7.41% and 11.11% at tillering, booting and milking stages respectively, with significantly higher yield of 28.27 g/pot as compared to untreated control pots.